4(x-2)=6(2x+5)

Simple and best practice solution for 4(x-2)=6(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)=6(2x+5) equation:



4(x-2)=6(2x+5)
We move all terms to the left:
4(x-2)-(6(2x+5))=0
We multiply parentheses
4x-(6(2x+5))-8=0
We calculate terms in parentheses: -(6(2x+5)), so:
6(2x+5)
We multiply parentheses
12x+30
Back to the equation:
-(12x+30)
We get rid of parentheses
4x-12x-30-8=0
We add all the numbers together, and all the variables
-8x-38=0
We move all terms containing x to the left, all other terms to the right
-8x=38
x=38/-8
x=-4+3/4

You can always share this solution

See similar equations:

| v+9/3=-3 | | 2(11x+5)=4x-8 | | 37+13x-26=180 | | 2(½q+1)=-3(2q-1)+4(2q+1) | | 8x+3(x-5)=2x+3 | | 5x-4/9=8 | | 2x^2-4x+52=0 | | t²-6t=27 | | 1/3(9x–12)+2(5x–1)=1/4(8x+12)–3(2x+3) | | x-4x-16=0 | | 33=1+8a | | 3(x-8)=4(8-x) | | | | | | 1/3x+2x=-4 | | 4x-15=2x+35=90 | | x+18+4x=-34 | | 24=9+5p | | 13+x=4x+12 | | 6-5x=9x-10x-6= | | 0.04^x=1.024×10^-7 | | x+18+4x-34=9 | | 7x+63=89 | | 2m-3(2m-3)=45 | | i+7/9=3 | | 152+(x/4)=180 | | -4(2x+5)=5x-1=-48 | | -20-16u=-4(4u+5) | | x(2)=9(2)-5 | | 15x²-44x-21=0 | | ?2w?^2-w-15=0 | | 64a+2304=4608 | | X(3x+10)=3000 |

Equations solver categories